The Practicality and Effectiveness of the Chemical Snakes and Ladders Game on Acid-Base Material on the Learning Outcomes of Class XI SMA/MA Students - Lantusia, Marina; Iswendi, Iswendi (FKIP-Universitas Riau, 2023)
This research was motivated by the availability of the chemical ladder snake game as a medium for learning acid-base material developed by Amalia Putri Lubis & Iswendi. It is valid but not tested for practicality and effectiveness. This study aims to determine the suitability and effectiveness of the chemical snakes and ladders game. This type of research is a continuation of development research with a Pretest-Posttest Control Group Design and is a 4-D model development. The research population is class XI MIPA students of SMAN 1 Ranah Batahan. Samples take using by Simple Random Sampling technique. The research instruments were useful questionnaires and learning achievement tests. The data analysis technique is the practicality percentage technique and the N-Gain test and t-test. The results of the data analysis of practicality are, at a convenient level, for effectiveness the results of data analysis show pretty effective. This is evidenced by the N-Gain percentage of the experimental class of 66% at a somewhat adequate level and the control class of 47% at a less practical level, and supported by hypothesis testing with the t-test, namely tcount (2.6686)> table (2.0106) at the real level α = 0.05 with dk = 48 and chance t0.95.